A complexity scoring model for evaluating complexity of software projects. (23rd February 2023) - Damasiotis, Vyron; Fitsilis, Panos
This research identifies project factors that contribute to project complexity based on the analysis of ten project management subject areas, and of one subject area which is focusing on software development process factors. Subsequently, a project complexity model based on these factors that can be used for assessing the project complexity is presented. This enables organisations to evaluate projects' complexity at early phases, providing important knowledge that may be used for project selection. The followed approach acknowledges the endogenous character of complexity in projects but instead of trying to identify complexity characteristics in project results, it focuses on the complexity of project management processes. The proposed framework can be used for highlighting the most significant complexity areas acting as an important tool for better, more efficient, and more effective project management. The final step of this research is the validation of the proposed model using case studies.